2011
DOI: 10.1177/1545968311402508
|View full text |Cite
|
Sign up to set email alerts
|

Bimanual Training and Constraint-Induced Movement Therapy in Children With Hemiplegic Cerebral Palsy

Abstract: Both CIMT and bimanual training lead to similar improvements in hand function. A potential benefit of bimanual training is that participants may improve more on self-determined goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
297
8
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(320 citation statements)
references
References 39 publications
7
297
8
8
Order By: Relevance
“…However, decision points or guidelines for progression or adaptation of the intervention based on individual participants' response to therapy were described by a few studies (Charles, Wolf, Schneider, & Gordon, 2006;Elvrum, Braendvik, Saether, Lamvik, Vereijken, & Roeleveld, 2012;Gordon, Schneider, Chinnan, & Charles, 2007;Gordon, Hung, Brandao, Ferre, Kuo, Friel et al, 2011). One study of resistance training and Botulinum Toxin injections described the grading of the program: "Once the participants were able to perform three sets of ten repetitions in an exercise, intensity was build up progressively on an individualized basis by increasing the weights by 0.25 -0.5kg."…”
Section: Research Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, decision points or guidelines for progression or adaptation of the intervention based on individual participants' response to therapy were described by a few studies (Charles, Wolf, Schneider, & Gordon, 2006;Elvrum, Braendvik, Saether, Lamvik, Vereijken, & Roeleveld, 2012;Gordon, Schneider, Chinnan, & Charles, 2007;Gordon, Hung, Brandao, Ferre, Kuo, Friel et al, 2011). One study of resistance training and Botulinum Toxin injections described the grading of the program: "Once the participants were able to perform three sets of ten repetitions in an exercise, intensity was build up progressively on an individualized basis by increasing the weights by 0.25 -0.5kg."…”
Section: Research Interventionsmentioning
confidence: 99%
“…workshops) was reported in 17 studies (28%), however, no study reported adequate details about the content or structure of training, whether there were training materials or where these could be accessed. A further 10 studies (17%) reported having procedure manuals, generic or standardized task specific therapy protocols Duncan, Shen, Zou, Han, Lu, Zheng et al, 2012;Fehlings, Rang, Glazier, & Steele, 2000;Gordon et al, 2011;Kawamura, Campbell, LamDamji, & Fehlings, 2007;Klingels et al, 2013;Olesch, Greaves, Imms, Reid, & Graham, 2010;Rameckers, Speth, Duysens, Vles, & Smits-Engelsman, 2009;Speth, Leffers, JanssenPotten, & Vles, 2005) to guide clinicians in the provision of therapy, however only three provided details that the protocols could be accessed on request (Duncan et al, 2012;Olesch et al, 2010;Sakzewski et al, 2015).…”
Section: Research Interventionsmentioning
confidence: 99%
“…This kind of research is a necessary prerequisite to develop individually tailored intervention programs, striving to achieve the optimal benefit for individual children to whom rehabilitation measures are offered. Relations between maternal interactive behavior and mastery motivation in children with developmental disabilities The Miller et al 1 study is of interest because it provides evidence that consistent and positive parental discipline is related to mastery motivation, an important aspect of child development. Mastery motivation is a multifaceted, psychological force that stimulates the child's attempt to master tasks that are moderately challenging.…”
mentioning
confidence: 99%
“…4 The book 'From Neurons to Neighborhoods' identifies mastery motivation as a key developmental concept, which should be assessed as part of a child's evaluation. 3 The article by Miller et al 1 demonstrates that inadequate parenting relates cross-sectionally to lower mastery motivation for school-aged children with congenital hemiplegia, using the parental report Dimensions of Mastery Questionnaire (DMQ). With cross-sectional studies it is less possible to know whether maternal behavior has an effect on children's motivation than with a longitudinal study design.…”
mentioning
confidence: 99%
“…231 Activity-based practice in the context of ecologically friendly environments such as the preschool 5 and home 116 or in intensive day camps 232 and with motivating themes 217,233 appear to be key ingredients to successful training of unimanual capacity and compliance with the constraint. 234 Our own study, the "INCITE" trial, employed a novel circus theme during the activity based day camps to ensure practice with the 'just right challenge'…”
Section: (Ii) Infant Modified Constraint Induced Movement Therapymentioning
confidence: 99%